THE INFLUENCE OF PROMOTION THROUGH INSTAGRAM SOCIAL MEDIA AND PRICE ON CUSTOMER LOYALTY (A CASE STUDY OF RANDANG PAKU IKAN RANGKITO CONSUMERS) - Agnie Ramadhani; Annur Fitri Hayati (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
The goal of this study was to ascertain the impact of price and social media advertising on Randang Paku Pangkito customers' loyalty in Dharmasraya Regency. Descriptive quantitative study is what we're doing here. The participants in this study are Randang Paku Rangkito consumers. On the Chocran formula was used to determine the number of research samples. A total of 100 individuals were chosen using the purposive sampling method. The information used was gathered by the distribution of questionnaires with predefined questions to Randang Paku Rangkito customers. Multiple regression analysis using SPSS 21 is the analysis method employed. The study's findings demonstrate that: (1) Instagram social media promotion has a favorable and significant impact on Price has a positive and substantial impact on both consumer loyalty and (2) price has a positive and significant impact on both consumer loyalty and (3) promotion through social media platforms like Instagram.